The antibacterial effect of silver, zinc-oxide and combination of silver/ zinc oxide nanoparticles coating of orthodontic brackets (an in vitro study) - Noha K. Zeidan; Nagwa M. Enany; Gehad Genidy Mohamed; Eiman S. Marzouk (BMC, 2022)
Abstract Background Preventive measures are essential during the length of orthodontic treatment to reduce the risk of decalcification and white spot lesions formation. With the evolution of procedures that enable coating of the orthodontic brackets using nanoparticles known for their good antibacterial activity, coating the brackets with nanoparticles of silver, zinc oxide and combination of silver and zinc oxide to evaluate their antibacterial effect in comparison to a control group without coating was carried out in this study. Methods Four groups of 12 brackets each were included in the study. The coating procedure was carried out using physical vapor deposition. The antibacterial activity was tested on Streptococcus mutans and Lactobacillus Acidophilus using colony forming count. The antibacterial activity was evaluated immediately after coating and later after 3 months. Results Brackets coated with combination of silver and zinc oxide nanoparticles had the highest ability on reduction of both Streptococcus mutans and Lactobacillus Acidophilus count followed by silver nanoparticles and then zinc oxide nanoparticles. No significant difference was found between the first and second antibacterial tests. Conclusion The silver/zinc oxide nanoparticles coated brackets had the highest antibacterial effect in comparison to silver nanoparticles and zinc oxide nanoparticles individually coated brackets on Streptococcus mutans and Lactobacillus acidophilus, and all types of coatings showed enhanced antibacterial effect in comparison to the uncoated bracket. Coating of orthodontic brackets could be further assessed in clinical application to prevent decalcification.